On the structure of generalized Appell sequences of paravector valued homogeneous monogenic polynomials - Cruz, Carla (2012)
The fact that generalized Appell sequences of monogenic polynomials in the setting of hypercomplex function theory also satisfy a corresponding binomial type theorem allows to obtain their explicit structure. Recently it has been obtained a complete characterization in the case of paravector valued homogeneous polynomials of three real variables. The aim of this contribution is the study of paravector valued homogeneous polynomials of four real variables, where new types of generalized Appell sequences could be detected.